2015
DOI: 10.1371/journal.pone.0128534
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Oral Microbiota in Children with or without Dental Caries

Abstract: BackgroundThe aim of this longitudinal study was to evaluate the oral microbiota in children from age 3 months to 3 years, and to determine the association of the presence of caries at 3 years of age.Methods and findingsOral biofilms and saliva were sampled from children at 3 months (n = 207) and 3 years (n = 155) of age, and dental caries was scored at 3 years of age. Oral microbiota was assessed by culturing of total lactobacilli and mutans streptococci, PCR detection of Streptococcus mutans and Streptococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
80
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(109 citation statements)
references
References 48 publications
11
80
0
1
Order By: Relevance
“…HOT 431, Lactobacillus , Atopobium genus, A. parvulum , Actinobaculum sp. HOT 513, culture, HTS, microarray[49]M/F 3–3 MY L. hofstadii /Leptotrichia sp. HOT 203 or 234Healthy, CFPlaque, biofilm, saliva, mouth C. concisus , G. adiacens , Actinomyces sp.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…HOT 431, Lactobacillus , Atopobium genus, A. parvulum , Actinobaculum sp. HOT 513, culture, HTS, microarray[49]M/F 3–3 MY L. hofstadii /Leptotrichia sp. HOT 203 or 234Healthy, CFPlaque, biofilm, saliva, mouth C. concisus , G. adiacens , Actinomyces sp.…”
Section: Figurementioning
confidence: 99%
“…Since previous reviews [2,3], Leptotrichia species have been reported in >124 cases [4,7,16,1869,8793], whereby 30 cases involved L. buccalis [4,8,15,21,34,52,56,70–79,87], 24 cases L. wadei [4,20,24,34,37,42,48,56,67,80,81,90,93], 16 cases L. trevisanii [4,5,9,10,13,14,17,37,87], 14 cases L. hofstadii [34,40,49,56,8184,93], 10 cases L. goodfellowii [4,11,12,21,56,74,85,87], eight cases L. hongkongensis [4,6,18,45,47,56], and five L. shahii [34,56,86]. L. trevisanii and L. wadei bacteremia are extremely rare; clinicians should consider these species in cases involving immunocompromised patients with oral lesions [4,5,13,17,87].…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations